Applications of agent-based models and nonlinear econometrics in finance - Demary, Markus (print, 2010)
This dissertation contains applications of agent-based financial market models and nonlinear econometric methods in financial economics. The first part deals with the analysis of the effectiveness of currency transaction taxes within financial market models with traders with heterogeneous investment horizons who use fundamental and trend-chasing trading rules to determine their demands for foreign currency. The analysis comes to the result that small taxes levied on currency transactions have the potential to reduce mispricings by crowding out short-term traders and destabilizing trend-extrapolating trading rules. However, mispricings increase for larger tax rates, since their harm the stabilizing fundamental trading rules, too. The second part deals with the econometric estimation of speculative dynamics. I find empirical evidence for similar speculative dynamics as implied by the agent-based financial market model of Lux (1995).
Internetausg.: http://eldiss.uni-kiel.de/macau/receive/dissertation_diss_00005444
Keywords: Graue Literatur; Hochschulschrift; Tobinsteuer; Anlageverhalten; Institutioneller Investor; Devisenmarkt; Wechselkurs; Volatilität; Wirkungsanalyse; Simulation; Agentenbasierte Modellierung; Nichtlineare Dynamik; Theorie; Kaufkraftparität; Währungsspekulation; Statistische Verteilung; Chaostheorie; Schätzung; EU-Staaten